Let’s open our eyes to the importance of vaginal microbiota. Correlation between dysbiosis and HPV infection: A review - Patrycja Kostrzewa; Michał Kostrzewa; Maciej Sergiusz Anioł; Anna Palmerska; Andrzej Piela; Kinga Piela; Olga Katarzyna Przybyła; Anna Szurma; Rafał Szurma; Szymon Pacek (Journal of Education, Health and Sport, 2024)
Infections with the human papillomavirus (HPV) are one of the most common sexually transmitted diseases and are the main cause of precancerous changes and cervical cancer development. However, mere infection does not guarantee the development of disease or carcinogenesis. For this to occur, high-risk types of HPV must integrate into the host cell genome, transitioning into a persistent form of infection.